Patrones de comunicación parental y su influencia en el rendimiento escolar de los alumnos que son atendidos en el CAPS de la parroquia de Cutuglagua - Villalva Salguero, Karen Alejandra (2018)
In the present work, research is carried out on the influence of parental communication patterns on children's school performance. For this purpose, an analysis of the forms of communication and their impact on school performance is made. The methodology used is quasi-experimental, with no control group where the intervention group was composed of five couples with their respective children, who were trained in an assertive communication workshop for five sessions. The results of the intervention show that the forms of communication between the parents and the children were modified, with changes in the patterns of conflict resolution in the couple and their impact on healthy communication at home, emphasizing the role exercised by each member of the family. Recommendations are proposed to address inte